Ursodeoxycholic acid for the prevention of gallstone disease after bariatric surgery - Alexander V. Smirnov (Eco-vector, 2021)
Background: The development of gallstone disease (GSD) after bariatric surgery is a significant problem. The prophylactic effect of ursodeoxycholic acid (UDCA) preparations on the occurrence of cholelithiasis after gastric bypass and longitudinal gastrectomy has been studied. Aims: The aim of the study was to evaluate the effectiveness of ursodeoxycholic acid preparations in the prevention of cholelithiasis in patients after bariatric surgery. Methods: The results of a year-long follow-up for 128 patients after bariatric surgery were analyzed. In 68 patients, the prophylaxis of the gallstone disease development was not performed. 60 patients took a daily 500 mg dose of UDCA orally. Results: Cholelithiasis had developed in 17 (25%) patients who did not undergo the prophylaxis of cholelithiasis. Of these, 10 (14.7%) underwent cholecystectomy. Among those patients who took UDCA drugs, stones in the gallbladder were found in 7 (11.6%), and only one patient (1.7%) required a surgical treatment. Conclusion: UDCA administration during the first year after bariatric surgery in the amount of 500 mg per day significantly reduces the likelihood of the de novo cholelithiasis development. The medical prophylaxis of gallstone disease should be included in the standards of bariatric patients' management.